Living Conditions in Timber Houses: Emission Trends and Indoor Air Quality - Fürhapper, Christina; Habla, Elisabeth; Stratev, Daniel; Weigl, Martin; Dobianer, Karl (Frontiers in Built Environment, 2020)
Indoor air quality (IAQ) was investigated in 13 newly-built, occupied timber houses on a long-term basis. The study included a comparison of the construction types timber-frame (TF) and solid wood (SF), in addition two different ventilation types, controlled vs. window ventilation, were contrasted. The emission progression of volatile organic compounds (VOCs) including formaldehyde, was recorded and compared with the subjective well-being of the residents, which was identified by use of standardized questionnaires. This was completed with toxicological assessment and repeated measurements of specific medical parameters of health indicative character. It was found that VOC-emissions were initially elevated regardless of construction and ventilation type. However, after a period of up to 8 months emissions mostly decreased to an average level. Whereas the SW constructions released distinctly more terpenes compared to the TF houses, there was no significant difference regarding the total concentration of emitted VOCs. The use of controlled ventilation systems resulted in lower VOC-concentrations and thus in higher IAQ compared to window ventilation. From a toxicological point of view the major part of the investigated houses were unobtrusive and IAQ was considered as “high” or “satisfactory”. Residents were continuously very satisfied with their health and quality of life. This perception was confirmed by the results gained from the accompanying medical examinations, giving no indication for physical impairments.